An investigation on the effects of increasing maximum wind speed of tropical cyclones on the return periods of water levels in the sea area of the Yangtze River Delta - Pan, Yi; Li, Weihan; Tan, Jiahui; Yu, Pubing; Chen, Xinping; Chen, Yongping (Frontiers in Marine Science, 2023)
The impacts of increasing maximum wind speed of tropical cyclones on the return periods of water levels in the sea area of the Yangtze River Delta (including the Yangtze River Estuary and the Hangzhou Bay) are investigated with a series of numerical experiments. All tropical cyclones that impact the Yangtze River Delta from 1949 to 2019 are picked out and used to drive the storm surge model of the Yangtze River Delta to get the historical water levels in the sea areas of the Yangtze River Delta. Together with the simulated astronomical tidal levels during 1949 to 2019, the extreme water levels of different return periods are calculated. Then the maximum wind speeds of the selected tropical cyclones are enlarged by 11% according to the expected increasing amount under global climate change, and then the extreme water levels of different return periods under the scenario (with increased maximum wind speed) are calculated with the same procedure. With the extreme water levels calculated with the historical tropical cyclones and enhanced tropical cyclones, the effects of increasing maximum wind speed of tropical cyclones on the increases of extreme water levels and the decrease of return periods are analyzed. The results show that the responses of the extreme water levels and the corresponding return periods in the inner area of the estuaries are more sensitive to the increasing maximum wind speed of tropical cyclones compared to that in the outer areas of the estuaries. The responses of the extreme water levels and the corresponding return periods in the Yangtze River Estuary and the Hangzhou Bay also shows different characteristics. The results are of reference significance to the management of future coastal disaster prevention and mitigation in the Yangtze River Delta and the methodology can also be used in other estuaries to investigate the potential impacts of changes in climate and hydrology factors on extreme water levels and the corresponding return periods.